The Problem of Rationality in Sociology (II) - Valantiejus, Algimantas (Sociologija. Mintis ir veiksmas, 2013)
The second part of the article aims to articulate and explicate the parallels between post-empiricist scientific philosophy and post-analytical sociology, and between the conception of naturalistic epistemology in philosophy and the conception of pragmatic rationality in sociology. The article argues that the methodological problem of rationality in sociology is the part of the larger epistemological relationship between philosophy and science. Normative relationship between the norms of rationality and the criteria of scientific objectivity is analyzed in two main perspectives of contemporary sociology – analytical and post-analytical.